Proliferative ameloblastomatous calcifying cystic odontogenic tumor of the mandible: A rare histological variant - Kamala Rawson; Basavaraj N Kallalli; Nimesh Patel; Yatriben Sandesara (Wolters Kluwer Medknow Publications, 2015)
Calcifying cystic odontogenic tumor (CCOT) is an extremely rare clinical entity. It was considered as a cyst until 2005, when World Health Organization included it among the odontogenic tumors. It presents as a slow-growing, painless swelling of the jaw. Radiographically, it may be seen as a unilocular or multilocular radiolucency. Here, we present a case of a proliferative ameloblastomatous type of CCOT of the left mandible. Conventional radiography and cone beam computed tomography were performed, in which the lesion was found to be unicystic without any sign of calcification. The lesion was also associated with an impacted 37 tooth, which was displaced to the inferior border of the mandible.